Diurnal bird raptors of Llanos de Moxos, Bolivia - Daniele, Gonzalo (2018)
Raptor abundance has been poorly documented in the Neotropics. Here we describe the abundance and composition of the diurnal bird raptor community of Llanos de Moxos, one of the largest and less studied Neotropical savannah. During four consecutive breeding seasons (i.e., August 2007 to February 2008, August 2008 to January 2009, August 2009 to January 2010, and August 2010 to January 2011), we monitored 11 transects and 30 points, searching for raptors’ activity. We detected 29 diurnal bird raptor species in the region, which represented almost half of diurnal bird raptor species of Bolivia. As expected, scavengers and generalists were most frequent and abundant diurnal bird raptors. The Llanos de Moxos shared 83% of raptor species with Venezuelan Llanos and 67% with Chaco wetlands. The Llanos de Moxos is an important migratory and conservation region for some species as Swainson’s hawk, Chaco eagle, osprey and peregrine falcon. The lack of effective protected areas in the region is concerning, and, thus, the establishment of such areas should be a conservation priority.